Some pharmacoeconomic aspects of congestive heart failure in Slovenia - Modrijančič, Mojca (Zdravniški vestnik, 2004)
Background. Congestive heart failure is a fatal disease. In view of its increasing frequency, primarily in the developed world and its aging population, it is becoming a major economic burden for the health care and whole society. Methods. A meta-analysis of effectiveness of convertase inhibitors and beta-blockers in the treatment of congestive heart failure was made. Based on epidemiological data collected in the region Bela krajina, we theoretically calculated the prevalence of congestive heart failure in Slovenia, visits at specialist doctors in a year, and determined hospitalization level. Also, we calculated the annual costs for each individual patient according to the classification made by the New York Heart Association (NYHA), total therapy costs for all patients with heart failure inSlovenia, the share of these costs in the total health care expenditures in Slovenia and in the gross national product. Results. Meta-analysis revealed effectiveness of the treatment of patients with heart failure with convertase inhibitors and beta-blockers with regard to reduced mortality as well as reduction of number of hospitalizations. Based on the epidemiological data from the region Bela krajina, the calculated prevalence of heart failure in the Slovene population was 1.11%, and the heart failure hospitalization level 1.37%. The annual costs of treatment of an individual patient with heart failure are increasing with progressive NYHA classes and amount to SIT 147,000.00 in NYHA class I, and SIT 1,672,000.00 in NYHA IV. Total costs of optimum treatment of the 40,000 patients with heart failure would in Slovenia amount to SIT 22,559,570,750.00, accounting for 7.07% of total health care expenditures and 0.56% of the gross national product. Conclusions. Prevalence of heart failure increases with age and is a considerable economic burden for the society.
Keywords: cardiovascular disease; epidemiologija; farmakoekonomika; kardiovaskularne bolezni; srčno popuščanje; therapy; zdravljenje